RECONFIRMING THE SPECIES OF MUD CRAB GENUS SCYLLA (DE HAAN, 1833) IN BALIKPAPAN, EAST KALIMANTAN PROVINCE, INDONESIA BASED ON MITOCHONDRIAL 16S rRNA - Andi Parenrengi; Gunarto Gunarto; Sulaeman Sulaeman; Andi Tenriulo; Herlinah Herlinah (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2020)
Taxonomy of mud crab species under the genus Scylla has been misidentified for several years due to their high morphological similarity. In Indonesia, some reports concerning mud crab have been published with misleading identification results where the species under the genus Scylla all named as Scylla serrata. The study was conducted to reconfirm the validity of species in the mud crab genus Scylla collected from Balikpapan mangrove, East Kalimantan, Indonesia and to analyze the genetic variation of the first generation (G-1) offspring, based on mitochondrial 16S rRNA sequence. The animal test used for species identification was a representative sample of mud crab. Ten of the G-1 crablet were randomly sampled for genetic variation analysis. Fragment of the 16S rRNA gene was isolated by PCR technique and purified for sequencing purpose. The mtDNA sequences were analyzed using Genetyx, BLAST-N, and DnaSP to get a consensus sequence, similarity index, haplotype and sequence diversity, and the number of haplotypes. The results showed that the 16S rRNA gene was successfully isolated with a single band in size of approximately 600 bp. The mud crab morphologically identified as Scylla tranquebarica was genetically confirmed as a species of S. tranquebarica. High haplotype diversity (0.9254) and low nucleotide diversity (0.1256) were revealed in the G-1 mud crab population, while the number of haplotypes was 7.5.